2004
DOI: 10.1016/j.ymthe.2004.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Bystander activity of Ad-mda7: Human MDA-7 protein kills melanoma cells via an IL-20 receptor-dependent but STAT3-independent mechanism

Abstract: The melanoma differentiation-associated gene-7 (mda-7/IL24) is a unique member of the IL-10 family of cytokines, with ubiquitous tumor cell proapoptotic activity. Transduction of tumor or normal cells with the mda-7 gene results in secretion of glycosylated MDA-7 protein. Recent data indicate that secreted MDA-7 protein functions as a pro-Th1 cytokine and as a potent antiangiogenic molecule. MDA-7 protein binds two distinct type II cytokine heterodimeric receptor complexes, IL-20R1/IL-20R2 (type 1 IL-20R) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
110
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(119 citation statements)
references
References 37 publications
9
110
0
Order By: Relevance
“…Differences in tumor size were analyzed for significance by the Student's t-test. Enhanced in vitro growth inhibitory and cytotoxic activity of Ad-mda7 and Herceptin in Her-2 þ breast cancer cells The antiproliferative effects of Ad-mda7 in various cancer cell types have been demonstrated in previous studies; [16][17][18][19][20][21][22][24][25][26][27][28][29][30][31][32][33][34]36 and the relevance of these findings to the clinical setting is supported by in vivo lung and breast xenograft models. 17,21 To corroborate that the Her-2 receptors expressed by the breast cancer cells are functional, we evaluated cell death in MDA-MB-453 and MCF-7 lines treated with increasing amounts of Herceptin (0-100 mg/ ml).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Differences in tumor size were analyzed for significance by the Student's t-test. Enhanced in vitro growth inhibitory and cytotoxic activity of Ad-mda7 and Herceptin in Her-2 þ breast cancer cells The antiproliferative effects of Ad-mda7 in various cancer cell types have been demonstrated in previous studies; [16][17][18][19][20][21][22][24][25][26][27][28][29][30][31][32][33][34]36 and the relevance of these findings to the clinical setting is supported by in vivo lung and breast xenograft models. 17,21 To corroborate that the Her-2 receptors expressed by the breast cancer cells are functional, we evaluated cell death in MDA-MB-453 and MCF-7 lines treated with increasing amounts of Herceptin (0-100 mg/ ml).…”
Section: Discussionmentioning
confidence: 81%
“…[18][19][20][21][22][23]38 It is now known that mda-7 activates various signaling pathways in a cell-type-specific manner, and that these pathways ultimately converge on mitochondrial destruction and induction of apoptosis. 21,22,[24][25][26][27][28][29][30] However, in spite of its clear tumor-suppressive effects, the mechanisms by which Ad-mda7 induces cytotoxicity have not been fully characterized. Our group has previously demonstrated that Ad-mda7, as a single agent therapy, induces apoptosis and inhibits growth in pancreatic, lung and breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…These include inhibition of tumor cell invasion and migration, 34,35 potent antiangiogenic effects, 36,37 immune stimulatory activity 38,39 and direct bystander cytotoxicity. 40 In recent studies, a phase I clinical trial was initiated using intratumoral injections of nonreplicating adenovirus vector harboring the mda-7/IL-24 gene (Admda-7; INGN 241). INGN 241 can induce apoptosis in a large part of tumor volume following a single intratumoral injection.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the bystander effect is likely caused by secreted MDA-7/IL-24 protein and not by other secreted factor(s). It has been demonstrated that partially purified MDA-7/IL-24 protein, obtained from supernatants of HEK293 cells, induces apoptosis only in cancer cells in a receptordependent and STAT3-independent manner (29). A recent study demonstrated that purified MDA-7/IL-24 protein induces cell death in melanoma cells (29).…”
mentioning
confidence: 99%
“…It has been demonstrated that partially purified MDA-7/IL-24 protein, obtained from supernatants of HEK293 cells, induces apoptosis only in cancer cells in a receptordependent and STAT3-independent manner (29). A recent study demonstrated that purified MDA-7/IL-24 protein induces cell death in melanoma cells (29). However, a detailed analysis of the molecular mechanism underlying this effect was not performed.…”
mentioning
confidence: 99%